Cosmic Rays Report from the Structure of Space - A. Annila (Advances in Astronomy)
Spectrum of cosmic rays follows a broken power law over twelve orders of magnitude. Since ubiquitous power laws are manifestations of the principle of least action, we interpret the spectrum accordingly. Our analysis complies with understanding that low-energy particles originate mostly from rapidly receding sources throughout the cosmos. The flux peaks about proton rest energy whereafter it decreases because fewer and fewer receding sources are energetic enough to provide particles with high enough velocities to compensate for the recessional velocities. Above 1015.6 eV the flux from the expanding Universe diminishes below the flux from the nearby nonexpanding part of the Universe. In this spectral feature, known as the “knee,” we relate to a distance of about 1.3 Mpc where the gravitational potential tallies the energy density of free space. At higher energies particles decelerate in a dissipative manner to attain thermodynamic balance with the vacuum. At about 1017.2 eV a distinct dissipative mechanism opens up for protons to slow down by electron-positron pair production. At about 1019.6 eV a more effective mechanism opens up via pion production. All in all, the universal principle discloses that the broad spectrum of cosmic rays probes the structure of space from cosmic distances down to microscopic details.